Personality determinants of eating behaviours among an elite group of Polish athletes training in team sports - Gacek, M.; Wojtowicz, A.; Popek, A. (Nutrients, 2023)
The nutritional behaviours of athletes are determined by environmental and individual factors. The aim of the research was to analyse the personality determinants of the eating behaviour among an elite group of Polish athletes training in team sports. The research was conducted among 213 athletes, using a proprietary validated nutritional behaviour questionnaire and the Neuroticism Extraversion Openness-Personality Inventory-Revised (NEO-PI-R Personality Inventory). Statistical analysis was performed with the use of Pearson`s linear and Spearman`s signed rank correlation coefficients, as well as multiple regression evaluation, assuming the significance level of a = 0.05. It was shown that the overall index of proper eating behaviour increased with increasing neuroticism (r = 0.132) and decreased with increasing openness to experience (r = -0.143). When assessing individual nutritional behaviours, it was indicated, among others, that with increasing neuroticism, athletes more often avoided energy drinks (R = 0.173), and with increasing extraversion, they more frequently consumed vegetables at least twice a day (R = 0.154). At the same time, the consumption of raw vegetables (R = -0.153), 2-3 portions of vegetables and fruit per day (R = -0.157) and the limitation of sweet and salty snacks (R = -0.152) decreased along with an increase in openness. On the other hand, with increasing conscientiousness, the regular consumption of meals (R = 0.186), dairy products (R = 0.143) and the reduction of sweet and salty snacks (R = 0.148) increased. The model built on the basis of the Big Five personality traits explained, to a very large extent (approx. 99%), variance concerning the general index of normal eating behaviour among athletes. The predictive significance of the personality traits presented in the Big Five model was demonstrated in relation to the quality of nutritional choices among Polish athletes competitively training in team sports, which may be used to personalise the dietary education of athletes.